2013
DOI: 10.5120/11971-6640
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Intrusion Detection Model based on Machine Learning Techniques

Abstract: Intrusion detection continues to be an active research field. Even after 20 years of research, the intrusion detection community still faces several difficult problems. Detecting unknown patterns of attack without generating too many false alerts remains an unresolved problem. Although recently, several results have shown that there is a potential resolution to this problem. Anomaly detection is a key element of intrusion detection in which perturbations of normal behavior suggest the presence of intentionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this section, related works with an emphasis on the ML approach for IDS were examined and discussed. The following are some of these studies: Omar et al [9] suggested an amalgam ML approach for intrusion detection that combines unsupervised and supervised classi cation algorithms and employs K-means, fuzzy C-means, and GSA clustering procedures to achieve identical patterns of a handler's operation. The proposed method's detection accuracy is then improved by combining an SVM with a gravitational search procedure as an amalgam categorization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this section, related works with an emphasis on the ML approach for IDS were examined and discussed. The following are some of these studies: Omar et al [9] suggested an amalgam ML approach for intrusion detection that combines unsupervised and supervised classi cation algorithms and employs K-means, fuzzy C-means, and GSA clustering procedures to achieve identical patterns of a handler's operation. The proposed method's detection accuracy is then improved by combining an SVM with a gravitational search procedure as an amalgam categorization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Omar et al [9] the supervised and unsupervised classification methods are combined, the same patterns of a handler's action are achieved using K-means, filtering, and Gia segmentation approaches. This is really a hybrid method to machine learning for intrusion detection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this section, related works with an emphasis on the ML approach for IDS were examined and discussed. The following are some of these studies: Omar et al [9] suggested an amalgam ML approach for intrusion detection that combines unsupervised and supervised classification algorithms and employs K-means, fuzzy C-means, and GSA clustering procedures to achieve identical patterns of a handler's operation. The proposed method's detection accuracy is then improved by combining an SVM with a gravitational search procedure as an amalgam categorization.…”
Section: Literature Reviewmentioning
confidence: 99%